Food and nutrition education in Australian primary schools: Parents' perspectives on why, when and how. (18th January 2022) - Aydin, Gozde; Margerison, Claire; Worsley, Anthony; Booth, Alison
Abstract: We examined Australian parents' opinions of primary school food and nutrition education (FNE) via a cross‐sectional survey that collected quantitative and qualitative data. Most parents agreed that primary schools should teach FNE, starting at either the first or the second year of primary school and delivered weekly or fortnightly for approximately 1–2 h. The majority of parents believed that FNE could be incorporated into several school subjects. Many believed that FNE should be taught to ensure equity and to promote healthy eating among children. Consideration of parents' opinions about school FNE programmes could help design and deliver more effective FNE programmes.